USM WINS INAUGURAL NESTLE'S NESCAFE HUB UNIVERSITY PROGRAMME - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, December 2015 After a threemonth long competition, team Coffeebenders from the Universiti Sains Malaysia (USM) prevailed among other public and private universities in the inaugural Nestle’s Nescafe Hub University Programme 2015 (NHUP15).